Elastic, adhesive, and charge transport properties of a metal-molecule-metal junction the role of molecular orientation, order, and coverage - DelRio, Frank W (Langmuir : the ACS journal of surfaces and colloids, 2010)
The elastic, adhesive, and charge transport properties of a metal-molecule-metal junction were studied via conducting-probe atomic force microscopy (AFM) and correlated with molecular structure by near-edge X-ray absorption fine structure (NEXAFS) spectroscopy. The junctions consisted of Co-Cr-coated AFM tips in contact with methyl-terminated alkanethiols (CH(3)(CH(2))(n-1)SH, denoted by C(n), where n is the number of carbons in the molecular chain) on Au substrates. AFM contact data were analyzed with the Derjaguin-Muller-Toporov contact model, modified by a first-order elastic perturbation method to account for substrate effects, and a parabolic tunneling model, appropriate for a metal-insulator-metal junction in which the thickness of the insulator is comparable to the Fermi wavelength of the conducting electrons. NEXAFS carbon K-edge spectra were used to compute the dichroic ratio R(I) for each film, which provided a quantitative measure of the molecular structure as a function of n. As n decreased from 18 to 5, there was a change in the molecular phase from crystalline to amorphous (R(I) --> 0) and loss of surface coverage, and as a result, the work of adhesion w increased from 82.8 mJ m(-2) to 168.3 mJ m(-2), the Young's modulus of the film E(film) decreased from 1.0 to 0.15 GPa, and the tunneling barrier height phi(0) - E(F) decreased from 2.4 to 2.1 eV. For all n, the barrier thickness t decreased for small applied loads F and remained constant at approximately 2.2 nm for large F. The change in behavior was explained by the presence of two insulating layers: an oxide layer on the Co-Cr tip, and the alkanethiol monolayer on the Au surface. X-ray photoelectron spectroscopy confirmed the presence of an oxide layer on the Co-Cr tip, and by performing high-resolution region scans through the film, the thickness of the oxide layer t(oxide) was found to be between 1.9 and 3.9 nm. Finally, it was shown that phi(0) - E(F) is strain-dependent, and the strain at which the film is completely displaced from under the tip is -0.17 for all values of n